Harper's illustrated biochemistry - Murray, Robert K. (New York :;London : McGraw-Hill Medical ;;McGraw-Hill [distributor], 2009)
Comprehensive, concise, and up-to-date, Harper's is unrivaled in its ability to clarify the link between biochemistry and the molecular basis of health and disease. The Twenty-Eighth Edition has undergone sweeping changes -- including a conversion to full-color artwork and the substantial revision and updating of every chapter -- all to reflect the latest advances in knowledge and technology and to make the text as up-to-date and clinically relevant as possible. Combining outstanding full-color illustrations with integrated coverage of biochemical diseases and clinical information, Harper's offers an organization and clarity not found in any other text on the subject
Biochemistry & medicine -- Water & pH -- Amino acids & peptides -- Proteins: determination of primary structure -- Proteins: higher orders of structure -- Proteins: myoglobin & hemoglobin -- Enzymes: mechanism of action -- Enzymes: kinetics -- Enzymes: regulation of activities -- Bioinformatics & computational biology -- Bioenergetics: the role of ATP -- Biologic oxidation -- The respiratory chain & oxidative phosphorylation -- Carbohydrates of physiologic significance -- Lipids of physiologic significance -- Overview of metabolisms & the provision of metabolic fuels -- The citric acid cycle: the catabolism of acetyl-CoA -- Glycolysis & the oxidation of pyruvate -- Metabolism of glycogen -- Gluconeogenesis & the control of blood glucose -- The pentose phosphate pathway & other pathways of hexose metabolism -- Oxidation of fatty acids: ketogenesis -- Biosynthesis of fatty acids & eicosanoids -- Metabolism of acylglycerols & sphingolipids -- Lipid transport & storage -- Cholesterol synthesis, transport, & excretion -- Biosynthesis of the nutritionally nonessential amino acids -- Catabolism of proteins & of amino acid nitrogen -- Catabolism of the carbon skeletons of amino acids -- Conversation of amino acids to specialized products -- Porphyrins & bile pigments -- Nucleotides -- Metabolism of purine & pyrimidine nucleotides -- Nucleic acid structure & function -- DNA organization, replication, & repair -- RNA synthesis, processing, & modification -- Protein synthesis & the genetic code -- Regulation of gene expression -- Molecular genetics, recombinant DNA, & genomic technology -- Membranes: structure & function -- The diversity of the endocrine system -- Hormone action & signal transduction -- Nutrition, digestion, & absorption -- Micronutrients: vitamins & minerals -- Free radicals and antioxidant nutrients -- Intracellular traffic & sorting of proteins -- Glycoproteins -- The extracellular matrix -- Muscle & the cytoskeleton -- Plasma proteins & immunoglobulins -- Hemostasis & thrombosis -- Red & white blood cells -- Metabolism of xenobiotics -- Biochemical case histories
Previous edition: Stamford, Conn.: Appleton & Lange, 2006
Includes bibliographical references and index
Keywords: Biochemistry; Biochemistry -- Clinical biochemistry; Energy Metabolism -- Metabolism; Metabolism -- Energy metabolism